2013
DOI: 10.1177/0954406213509612
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on turning of AISI 1040 steel with the application of nano-crystalline graphite powder as lubricant

Abstract: The past few decades have witnessed significant advancements in turning processes, cutting tools and coolant/lubricant chemistry. These developments have enhanced the machining capabilities of hard materials when machining at higher cutting conditions. Turning, being characterized by the development of high temperatures at the cutting zone, is critical with respect to the tool life and surface finish apart from other machining results like the forces generated. This phenomenon of heat generation at the cutting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The outcome seems that the cutting fluid with novel MoS 2 nano-particles drastically reduce the friction and grinding force [9]. Several other researchers, namely Ramesh et al [10−12], Sridharan and Malkin [13], Kwon and Drzal [14], Nam et al [15], Samuel et al [16], Park et al [17], Vasu and Reddy [18], Ramesh et al [19], Khanderkar et al [20], Kalita et al [21], Nguyen et al [22], Amrita et al [23], Paul and Varadarajan [24], Srikiran et al [25], Amrita et al [26], Sharma et al [27], Su et al [28] and Gupta et al [5] have applied different nano fluids in various sorts of machining operations. Table 1 clearly describes that, the use of nano-particles with MQL in machining has proved to be an effective method to minimize the given responses.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome seems that the cutting fluid with novel MoS 2 nano-particles drastically reduce the friction and grinding force [9]. Several other researchers, namely Ramesh et al [10−12], Sridharan and Malkin [13], Kwon and Drzal [14], Nam et al [15], Samuel et al [16], Park et al [17], Vasu and Reddy [18], Ramesh et al [19], Khanderkar et al [20], Kalita et al [21], Nguyen et al [22], Amrita et al [23], Paul and Varadarajan [24], Srikiran et al [25], Amrita et al [26], Sharma et al [27], Su et al [28] and Gupta et al [5] have applied different nano fluids in various sorts of machining operations. Table 1 clearly describes that, the use of nano-particles with MQL in machining has proved to be an effective method to minimize the given responses.…”
Section: Introductionmentioning
confidence: 99%
“…Srikiran et al [159] studied the influence of nano-crystalline graphite mixed cutting fluid in turning operation of AISI 1040 steel workpiece material with lathe machine under three cutting conditions, i.e., dry, wet and solid lubricants. The different concentrations of nanographite considered were 0.25, 0.5, 2, 4, 6, 8 and 10% in SAE 40 oil.…”
Section: Turning Processmentioning
confidence: 99%
“…The surface roughness also affected by tool nose radius and decreases with increase in the nose radius of the cutting tool [15]. The application of graphite powder as a solid lubricant during turning of AISI 1040 steel was tested by Srikiran et al [16]. They observed that cutting forces increase with decrease in particles size whereas surface finish deteriorates due to the size of the solid graphite particles.…”
Section: A Research In Turning Of Ferrous Metas and Their Alloysmentioning
confidence: 99%